1987
DOI: 10.1113/jphysiol.1987.sp016681
|View full text |Cite
|
Sign up to set email alerts
|

Changes in presynaptic inhibition of Ia fibres at the onset of voluntary contraction in man.

Abstract: SUMMARY1. Two independent methods were used, in man, to assess changes in presynaptic inhibition of Ia terminals at the onset of selective voluntary contractions: (1) measurement of the amount of heteronymous monosynaptic I a facilitation (from the quadriceps muscle to soleus motoneurones) to provide an assessment of the amount of ongoing presynaptic inhibition exerted on the la fibres responsible for the facilitation; (2) measurement of the inhibition of H reflexes 40-60 ms after a short vibration to the tibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
233
2
6

Year Published

1996
1996
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 422 publications
(254 citation statements)
references
References 24 publications
13
233
2
6
Order By: Relevance
“…Previous human studies have demonstrated diverse excitatory inputs onto Ia and presynaptic inhibitory interneurons in man, with their inhibitory actions to decrease or to increase depending on the direction of the movement (Petersen et al 1999;Morita et al 2001;Kagamihara 1993, Pierrot-Deseilligny 1997;Hultborn et al 1987). These studies along with our findings suggest that the strength of reciprocal Ia and presynaptic inhibition is influenced by afferents of distal and proximal muscles and that some heteronymous connections postulated in healthy subjects (Meunier et al 1990) are preserved following SCI.…”
Section: Hip-induced Modulation Of Spinal Inhibitory Mechanismssupporting
confidence: 72%
“…Previous human studies have demonstrated diverse excitatory inputs onto Ia and presynaptic inhibitory interneurons in man, with their inhibitory actions to decrease or to increase depending on the direction of the movement (Petersen et al 1999;Morita et al 2001;Kagamihara 1993, Pierrot-Deseilligny 1997;Hultborn et al 1987). These studies along with our findings suggest that the strength of reciprocal Ia and presynaptic inhibition is influenced by afferents of distal and proximal muscles and that some heteronymous connections postulated in healthy subjects (Meunier et al 1990) are preserved following SCI.…”
Section: Hip-induced Modulation Of Spinal Inhibitory Mechanismssupporting
confidence: 72%
“…This stimulation, which can cause kinesthetic illusions of muscle lengthening, has also been demonstrated to have longer term effects after removal of the vibration (Cordo et al, 1995, Shinohara, 2005, Wierzbicka et al, 1998. These effects include increases in the discharge threshold of the Ia afferents and inhibition of Ia terminals (Hayward et al, 1986, Hultborn et al, 1987, Shinohara, 2005. Such vibration has been shown, in the ankle, to decrease the amplitude of H reflexes in both the stimulated and synergistic muscles (Curtis and Eccles, 1960, Hultborn et al, 1987, Shinohara, 2005.…”
Section: Discussionmentioning
confidence: 97%
“…These effects include increases in the discharge threshold of the Ia afferents and inhibition of Ia terminals (Hayward et al, 1986, Hultborn et al, 1987, Shinohara, 2005. Such vibration has been shown, in the ankle, to decrease the amplitude of H reflexes in both the stimulated and synergistic muscles (Curtis and Eccles, 1960, Hultborn et al, 1987, Shinohara, 2005. Such vibration exposure has been demonstrated to alter overall joint dynamics as well, with vibration of the ankle tendons, for example, altering center of pressure trajectories in standing sway after vibration exposure (Wierzbicka et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, testing PAD pathways by using sensory volleys during movements and posture in healthy or neurologically injured humans may monitor only part of the ongoing presynaptic inhibition (Butchart et al, 1993;Calancie et al, 1993;Earles et al, 2001;Bove et al, 2003;Kitano et al, 2009;Roche et al, 2011). Sensory stimulation studies should be complemented with other techniques, such as changes in heteronymous Ia facilitation (Hultborn et al, 1987a(Hultborn et al, , 1987b to evaluate the overall level of ongoing presynaptic inhibition (Faist et al, 1994(Faist et al, , 1996Morita et al, 1995Morita et al, , 2000Baudry et al, 2011).…”
Section: Presynaptic Inhibition and Movements In Humansmentioning
confidence: 99%